2019
DOI: 10.3390/min9050256
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of Methane within Chromitites of an Archean-Paleoproterozoic Greenstone Belt in Brazil

Abstract: Abiotic methane is widely documented in seeps, springs and aquifers associated with mafic-ultramafic rocks in Phanerozoic ophiolites, peridotite massifs and intrusions worldwide. Chromitites in ophiolites, in particular, have been interpreted as the rocks potentially generating methane though CO2 hydrogenation. Here, we document, for the first time, the presence of methane within chromitites in South America. We analyzed, through milling and gas extraction, the content of gas occluded in Cedrolina chromitite s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…The Cedrolina chromitite body is located within the lower stratigraphic units of the greenstone belt, where metakomatiites and metabasalts (talc-chlorite-schist, amphibolite and amphibole-schists) predominate over inter-bedded metasediments (metacherts, BIF). The chromitite has a tabular geometry of about 230 m × 100 m and 1-2.4 m thickness, being in contact with micaschists to the SE, and amphibole rich BIF to the NW [13,51]. At the scale of hand samples, the chromitite consists of rounded nodules, up to 1 cm in diameter, embedded in a matrix of chlorite and talc, with a mean modal composition of 60% chromite, 25% talc, and 15% Cr-rich chlorite.…”
Section: Cedrolina Ultramafic Body (Pilar De Goiás Greenstone Belt)mentioning
confidence: 99%
See 1 more Smart Citation
“…The Cedrolina chromitite body is located within the lower stratigraphic units of the greenstone belt, where metakomatiites and metabasalts (talc-chlorite-schist, amphibolite and amphibole-schists) predominate over inter-bedded metasediments (metacherts, BIF). The chromitite has a tabular geometry of about 230 m × 100 m and 1-2.4 m thickness, being in contact with micaschists to the SE, and amphibole rich BIF to the NW [13,51]. At the scale of hand samples, the chromitite consists of rounded nodules, up to 1 cm in diameter, embedded in a matrix of chlorite and talc, with a mean modal composition of 60% chromite, 25% talc, and 15% Cr-rich chlorite.…”
Section: Cedrolina Ultramafic Body (Pilar De Goiás Greenstone Belt)mentioning
confidence: 99%
“…Single crystals of chromite, variable in size from few microns up to 1 mm and, eventually, with hexagonal and octahedral shapes, have been also described [13,51], but are not shown in the pictures. According to these authors, the Cedrolina chromitite suffered intense metasomatism related to hydrothermal fluids emanated by albite-granite intrusions, which generated a complex suite of exotic accessory minerals such as monazite-Ce [52], uraninite, thorianite, and zircon.…”
Section: Cedrolina Ultramafic Body (Pilar De Goiás Greenstone Belt)mentioning
confidence: 99%
“…-Alkaline spring in Ranau where preliminary results showed that its water contains CH4 of potentially abiotic origin -Despite that no chromitites were found, the majority of Ranau peridotites are Lazar et al, 2012, Foustoukos et al, 2015, Portella et al, 2019. Moreover, awaruite is known to result from the breakdown of pentlandite from an alkaline Aluid (Garuti & Zaccarini 1997).…”
Section: Criteria From Partmentioning
confidence: 99%